2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591622
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain network analysis in schizophrenia using minimum spanning tree

Abstract: Schizophrenia is a mental disorder in which functional and structural brain networks are disrupted. Classical network analysis has been used by many researchers to quantify brain networks and to study the network changes in schizophrenia, but unfortunately metrics used in this classical method highly depend on the networks' density and weight; the comparisons made by this method are biased. The minimum spanning tree (MST) is an alternative method to solve this problem, but its usefulness in studying the schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…These results imply that the brain of IA participants developed for randomization. MaxDeg, MaxBC, and K are all indexes showing the existence of high‐degree nodes or hubs (Anjomshoa et al, ). These indexes’ values were higher in the IA group, suggesting some brain regions have a greater cognitive burden than comparable regions, which may ultimately be a risk factor for crucial node overloaded.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that the brain of IA participants developed for randomization. MaxDeg, MaxBC, and K are all indexes showing the existence of high‐degree nodes or hubs (Anjomshoa et al, ). These indexes’ values were higher in the IA group, suggesting some brain regions have a greater cognitive burden than comparable regions, which may ultimately be a risk factor for crucial node overloaded.…”
Section: Discussionmentioning
confidence: 99%
“…For each patient, 25 visual artifact-free and eyes closed (inspected by a clinical neurophysiologist) epochs of 4096 samples (8 seconds) were selected. The selected epoch has a band-pass filtered into the frequencies: delta (0.5-4 Hz), theta (4-8 Hz), lower alpha (8-10 Hz), upper alpha (10-12 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Because of the fact that different frequency ranges in alpha band are involved in different cognitive processes, 14 the alpha band was divided into 2 frequency bands.…”
Section: Eeg Recordingsmentioning
confidence: 99%
“…27,33 Furthermore, earlier schizophrenia studies using MST for diffusion tensor imaging (DTI) showed decreased centrality (low number of central hubs in the network) in several brain regions for the groups with psychotic disorders, 24 as well as differences in network organization between healthy controls and patients. 34…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rich evidence on specific cognitive dysfunction, not only as epiphenomenon due to therapy but core feature of the disease is currently been collected 1 . These cognitive changes have been discussed in association with neurodevelopmental theory and changes in brain circles, engaged in cognition, particularly these, related to prefrontal cortex and its networks to cortical and subcortical structures 2,3 .…”
Section: Introductionmentioning
confidence: 99%